The Usefulness of Peer Review for Selecting Manuscripts for Publication: A Utility Analysis Taking as an Example a High-Impact Journal - Bornmann, Lutz (Public Library of Science, 2010)
BACKGROUND: High predictive validity – that is, a strong association between the outcome of peer review (usually, reviewers' ratings) and the scientific quality of a manuscript submitted to a journal (measured as citations of the later published paper) – does not as a rule suffice to demonstrate the usefulness of peer review for the selection of manuscripts. To assess usefulness, it is important to include in addition the base rate (proportion of submissions that are fundamentally suitable for publication) and the selection rate (the proportion of submissions accepted). METHODOLOGY/PRINCIPAL FINDINGS: Taking the example of the high-impact journal Angewandte Chemie International Edition (AC-IE), we present a general approach for determining the usefulness of peer reviews for the selection of manuscripts for publication. The results of our study show that peer review is useful: 78% of the submissions accepted by AC-IE are correctly accepted for publication when the editor's decision is based on one review, 69% of the submissions are correctly accepted for publication when the editor's decision is based on two reviews, and 65% of the submissions are correctly accepted for publication when the editor's decision is based on three reviews. CONCLUSIONS/SIGNIFICANCE: The paper points out through what changes in the selection rate, base rate or validity coefficient a higher success rate (utility) in the AC-IE selection process could be achieved.